Supervisi Kepala Madrasah Dalam Menigkatkan Kualitas Mengajar Guru di Mts Rahmatullah Kou - Mardiani Masuku (Peneliti.net, 2023)
Implementation of adult education adapted to the culture of the nation and the global world. learning is the process of teaching in schools that organize. professional educators who do not only master the fields of science, methods,. The teaching and learning process at MTs Rahmatullah Kou is going well, but there are also things such as teacher performance that is not optimal in the teaching and learning process..As the results of observations (pre-research) by the author done with school principals and some teachers, there is a perception that teachers lack discipline in carrying out their duties such as not preparing Lesson Implementation Plans, low IT quality from teachers, and also lack of discipline in time, especially in terms of the implementation of the teaching and learning process..To overcome problems experienced by teachers at MTs Rahmatulah Kou is to carry out the role of supervision by the head of the Madrasah or supervisor .. In order to create qualified teachers who have special abilities and expertise in the field of teacher training so that they are able to carry out their duties and functions as teachers with maximum abilities In words On the other hand, qualified teachers are people who are well-educated and well-trained and have rich experience in their field. What is meant by educated and trained is not only having formal education but also having to master various strategies or techniques in teaching and learning as well as educational foundations as stated in teacher competence